Tech driven wellness: centralized integrated health management system in UAE - Dakwar, Mohamad Fadi; Dakwar, Norseen Fadi; Ali, Halah Yaseen; Shaker, Yomna O. (Institute of Advanced Engineering and Science, 2024)
With the ever-more increasing usage of technology in our day-to-day life, an incursion into healthcare has been warranted. Especially in today’s age, where you have digital trackers all around, confusing terms of service, and just in general difficult management of healthcare. HealthPulse seeks to revolutionize that and simplify the concept of healthcare to the simple person. This will be accomplished by integrating the application with the Emirates ID, in the United Arab Emirates, and granting access to various insurance and past records. Additionally, it features a section for early diagnoses and standard measurements, in addition to extensions and plugins to be provided by third parties. Using biometrics will apply in the implementation for the creation of a secure digital national ID and enhancing the merger of public. Machine learning framework, which is trained on a dataset of images of certain diseases will be able to differentiate between a healthy and inflicted cases.